Are all aspirations and expectations alike?: a longitudinal test of domain-specific effects of future beliefs on offending - Lee, Heejin (Journal of developmental and life-course criminology, 2024)
Major criminological theories contend that criminal behavior is affected by our perceptions of the future, including the goals we aspire to and our expectations about the possibility of achieving them. However, it is unclear whether aspirations or expectations have stronger influences on deviance. In addition, scant attention has been paid to the possibility that the effects of these perceptions depend on the domains of goals one values (e.g., education, career, family) or on the offense type. The current study uses seven years of data from the Pathways to Desistance study to examine these hypotheses. Modeling within-individual change in future beliefs over time, the findings support that some forms of aspirations and expectations decrease offending, whereas others have null effects. The aspiration for college education, the expectation of employment, and both related to lawful future selves are notable in crime reduction. Policy implications include the importance of structural opportunities and positive identity construction.